An improved and efficient synthesis of panobinostat. (1st September 2018) - Chen, Shanwen; Zhang, Peiming; Chen, Huali; Zhang, Pu; Yu, Yu; Gan, Zongjie
An improved and efficient method for the synthesis of panobinostat was developed. The commercially available starting material 4-(chloromethyl)benzaldehyde was converted to (E)-methyl 3-[4-(chloromethyl)phenyl]acrylate via the Wittig–Horner reaction and was then directly condensed with 2-(2-methyl-1H-indol-3-yl)ethanamine to afford the key intermediate (E)-methyl 3-[4-([2-(2-methyl-1H-indol-3-yl)ethyl]aminomethyl)phenyl]acrylate in a one-pot synthesis reactor. Subsequently a nucleophilic substitution reaction was carried out smoothly to generate the desired compound. The key intermediate and target compound were characterised by HRMS, 1H NMR and 13C NMR. This procedure is operationally simple and would be more suitable for industrial production.